ISOLASI DAN IDENTIFIKASI JAMUR PENGHASIL MIKOTOKSIN PADA BIJI KAKAO KERING YANG DIHASILKAN DI FLORES-LEMBATA - Emilia S.A. Wangge (Agriculture Faculty of Flores University, 2013)
A study entitled “Isolation and Identification of Mycotoxin-producing Fungi on Cocoa Beans Produced in Flores and Lembata” was done in order to know the population and species of fungi and to know the concentration of mycotoxin in the dried cocoa beans. The dry cocoa beans used in this study were collected from several locations in Flores. Isolation of the fungi was done using Sabouraud Dextrose Agar (SDA). Results of this study showed that there were several fungi were found in the dried cocoa beans produced in Flores, namely Aspergillus niger, A. flavus, A. parasiticus, A. fumigatusandMucor sp.